Genre analysis on concluding section of Malaysian applied linguistics research articles - Tang, Ping Wei (Universiti Malaysia Sarawak, UNIMAS, 2009)
This case study examined the structure and linguistics features of the concluding section of Malaysian Applied Linguistics research articles (RA). Based on the stratified random sampling, 50 RAs were obtained from the 8 journals. The move structures employed in these concluding sections were analysed by using the checklist adopted from Yang and Allison (2003). Meanwhile, the language features were analysed based on the checklist adapted from Allsop (1983), Bunton (2005), Huddleston and Pullum (2005), Swales (1981), Swales (1990), and Swales and Feak (2004). The results showed that 35 RAs had the heading of Conclusion, three with the heading of Discussions, two with Summary and the rest with different headings. There were 23 RAs containing all three obligatory moves including Summarize the study (M1), Evaluating the study (M2), and Deductions from the research (M3), 18 with M1 and M3, five RAs with M1 and M2, and the rest RA do not have all obligatory moves. There were 15 RAs with the move pattern of Summarize the study (M1) followed by Drawing pedagogical implication, (M1^M3S2). Besides, 14 RAs had the recycling moves and was dominated by recycling of Summarize the study (M1) which followed by Indicating significance (M2S1) with eight occurrences, [M1^M2S1]8.For the language features, 49 out of 50 RAs used modal verbs as hedging device. Moreover, the research also found that Malaysians writers had various choices for language features included the main verbs used to summarize the study, to indicate the limitations, and to recommend further research as well as the lexical phrases used to offer pedagogical implications. Among 49 RAs, 22 types of main verbs were found. The dominant main verbs used to summarize the study were show and reveal. However, only three types of main verbs were indentified to indicate the limitations of the study. The main verbs of limited, insufficient, and questioned were used as the indicators of limitation in the study. In order to recommend further research, nine main verbs were found to play the role of / informed the recommendations. The most common main verbs used to recommend further research was investigate. There were 26 examples were found to offer the pedagogical implications of the study. The common lexical phrases used to offer pedagogical implications were could provide, as guide, shed/ throw some light, and offers some important insights into. The results revealed more than half Malaysian RAs did not follow the move order as suggested by Yang and Allison (2003).